Molecular and Cellular Pathways as Treatment Targets for Biologic Therapies in Systemic Sclerosis - Dimitroulas, Theodoros; Daoussis, Dimitrios; Garyfallos, Alexandros; P. Sfikakis, Petros; D. Kitas, George (Current Medicinal Chemistry, 2015)
Recent advances have shed light on the complex pathogenic processes that underlie the development and progression of Systemic Sclerosis (SSc) but management of the disease remains problematic and curative treatment is not available. Better understanding of the underlying pathology has enabled novel therapeutic approaches to be investigated, as therapies in rheumatology are becoming increasingly disease/ organ-specific, targeting unique biological networks and signalling pathways. The pathophysiologic and clinical pleiomorphism of SSc however, represents a major barrier to conducting large well-controlled studies for the evaluation of non-selective immunosuppressive and novel highly selective agents. Therapeutic biologic strategies targeting inflammatory or profibrotic cytokines and lymphocyte activation proved to be efficacious in other systemic rheumatic diseases but have demonstrated contradictory results in SSc. Blocking of tumour necrosis factor alpha and interleukin-6 may improve SSc-associated arthritis, while depletion of B-cells may have benefits for skin and lung fibrosis, but randomized studies are needed. In this review we critically appraise available data for the treatment of SSc focusing on immunologic and antifibrotic strategies. Attenuation of the fibrotic process remains an unmet goal but the potential to prevent damage by promoting tissue repair has been shown in preclinical studies. Translation of these findings into clinical practice will hopefully establish new therapeutic options and improve prognosis of these patients, for which our therapeutic armamentarium remains poor.
Keywords: fibrosis